(untitled) (Research, Society and Development, 2021)
Unspecified non-organic psychotic disorders, also known as F-29, are hallucinatory or delusional disorders, as well as changes in thinking, becoming more disorganized, and personality. The study aims to report the experience of nursing students in the Systematization of Nursing Care to a patient withF-29 (non-organic and non-specific psychosis). This is a report of an experience of a qualitative nature, with a descriptive aspect, developed during the practice of the curricular component of mental health II, carried out in a referral hospital for psychiatric care in the city of Belém-PA, within a week, using the Marguerez arch. After collecting the first stage of the nursing process, it was possible to draw up diagnoses and interventions in order to provide the patient with a better prognosis and improve the practice and professional assistance to academics.Based on the above, it was possible to observe that nursing care within the patient’s pathological process is of paramount importance, especially in terms of encouraging its gradual improvement. Allied to this, it was possible to verify that the studies referring to this pathology in question are still few in the literary bases, for a more in-depth study and with more detail of information about it. That said, suggestions were made for future work such as:incorporation of pathophysiological aspects, effectiveness and impacts in face of the nurse’s performance and epidemiological aspects of the F-29.